2003
DOI: 10.1097/00000542-200311000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Ethical Approval and Informed Consent in Clinical Research Published in Leading Anesthesia Journals

Abstract: This study suggests that rates of IRB approval and informed consent vary among publications in anesthesia journals. Clearer guidelines (and author adherence) for all types of publication are needed, both as a protection for research subjects and to maintain public trust in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 19 publications
2
45
0
4
Order By: Relevance
“…The JMPT reported ethics approval in 95% of articles (80% for JCCA and 50% for CO), far above most other journals; for example, Matot et al 12 found a 29% failure to report ethics approval, and Karlawish et al 6 found close to 60% failed to report. Informed consent was reported slightly less (64% for JMPT, 40% for JCCA, and 17% for CO), and this is, with the exception of CO, in line with medical reports: 43%, 16 66%, 17 and 91%. 18 Although reporting ethics approval and consent is not a guarantee of overall ethical research, it provides means by which authors and journal editors assure the public they take seriously the reporting of ethical conduct of research.…”
Section: Discussionsupporting
confidence: 74%
“…The JMPT reported ethics approval in 95% of articles (80% for JCCA and 50% for CO), far above most other journals; for example, Matot et al 12 found a 29% failure to report ethics approval, and Karlawish et al 6 found close to 60% failed to report. Informed consent was reported slightly less (64% for JMPT, 40% for JCCA, and 17% for CO), and this is, with the exception of CO, in line with medical reports: 43%, 16 66%, 17 and 91%. 18 Although reporting ethics approval and consent is not a guarantee of overall ethical research, it provides means by which authors and journal editors assure the public they take seriously the reporting of ethical conduct of research.…”
Section: Discussionsupporting
confidence: 74%
“…Further, the Declaration stipulates that manuscripts that do not meet these principles “should not be accepted for publication” (article 27) 1. Smaller studies have suggested that not all published articles explicitly report informed consent or institutional review board or research ethics board (REB) approval 26. It has been proposed that if research does not clearly follow ethical standards and is accepted for publication on scientific merit, it should be accompanied by an editorial or comment highlighting the ethical questions raised 7 8.…”
mentioning
confidence: 99%
“…Facts about risks and burdens in comparison with foreseeable benefits to participants were realized in only 40% of the articles and even then were reported only as side effects. Our sample included a wider range of journals than earlier studies, 11,17 which may explain why ethics review was expected in only 55% of the journals. The publisher's ethics guidelines ranged from none to very detailed directions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Clearer guidelines on ethical reviews for all kinds of publications are needed. 11 Proxy consent by legal guardians is the requirement in neonatal research. This varies between countries concerning whether consent is needed from only one or both parents.…”
Section: Introductionmentioning
confidence: 99%